I hate fairyland. Volume one, Madly ever after - Young, Skottie (Image Comics, 2016)
Follow Gert, a forty year old woman stuck in a six year olds body who has been stuck in the magical world of Fairyland for nearly thirty years. Join her and her giant battle-axe on a delightfully blood soaked journey to see who will survive the girl who HATES FAIRYLAND.